Hydrographic changes in a river system and their influence on the legal classification of watercourses, exemplified by selected tributaries of the San river - Kubiak-Wójcicka, Katarzyna; Brózda, Sławomir; Sznajder, Agnieszka (Bulletin of Geography. Physical Geography Series, 2017)
The paper presents hydrographic changes in a river system and their influence on the legal classification of watercourses in Poland. As a case study, the watercourse Motwica, right tributary of the river San has been analysed. The main objective of this paper is an attempt to analyse whether the Motwica should be classified as flowing or standing water and the legal grounds for such classification in the Water Law act. On the base of archival and contemporary cartographic materials’ analysis it has been determined that the Motwica should not be classified as natural watercourse because its significant part flows in an artificial channel.